1979
DOI: 10.1524/ract.1979.26.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 34mCl and 38Cl Atoms Recoiling in Liquid Halobenzenes

Abstract: The reactions of radioactive chlorine atoms recoiling from two nuclear processes, "Cl(n, 2n)"'"a and "Cl(n, 7)"CI have been studied in different liquid halobenzenes. The ratio "Q-for-Cl vs.^'Cl-for-H yield for C^HjCl is dose-dependent, indicative for radiation-enhanced ^' Cl-for-Cl exchange. The Cl-for-Cl replacement yield is lowered on the addition of Ij, but much more for "CI than for It is suggested that the precursors to the exchange is a charge-transfer 7r-complex, rather than a a-complex. The fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 16 publications
7
50
0
Order By: Relevance
“…The yields are less than 1 % per H atom [8]. 4) Thermal '®Cl-for-Cl substitution yields are lower for monochlorotoluenes than for mono-and dichlorobenzenes due to the competitive abstraction of H from the CHa group which was also substantiated by addition experiments with I2 [9]. 5) The model proposed by KONTIS and URCH [12,13] is useful in the determination of the reactivity Parameters of recoil ^'Cl atoms in a variety of mixtures with chlorotoluenes [10,11] (KONTIS and GASPARAKIS [14] have recently extended this model to determine the cross-section parameters for the formation of dichlorobenzenes by measuring the individual product yields).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The yields are less than 1 % per H atom [8]. 4) Thermal '®Cl-for-Cl substitution yields are lower for monochlorotoluenes than for mono-and dichlorobenzenes due to the competitive abstraction of H from the CHa group which was also substantiated by addition experiments with I2 [9]. 5) The model proposed by KONTIS and URCH [12,13] is useful in the determination of the reactivity Parameters of recoil ^'Cl atoms in a variety of mixtures with chlorotoluenes [10,11] (KONTIS and GASPARAKIS [14] have recently extended this model to determine the cross-section parameters for the formation of dichlorobenzenes by measuring the individual product yields).…”
Section: Introductionmentioning
confidence: 98%
“…These studies were performed with the aim of gaining insight into the mechanisms of the hot and thermal substitution and abstraction processes as well as selectivity effects by measuring the total organic, substitution and Polymerie yields [3][4][5][6][7]. Chlorotoluenes, among the arenes, seem to provide valuable Information on these aspects and we have, therefore, undertaken a detailed investigation on the reactions of recoil "Cl atoms with these Compounds [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These findings clearly demonstrated that the presence of a second chlorine at different positions in an aromatic compound plays a prominent role in the substitution processes. BRINKMAN and coworkers have found that in 1 : 1 : 1 mixtures of isomeric dichlorobenzenes [5] and in the respective chlorotoluenes [4], the ο: m : ρ substitution yields were almost statistical, whereas the distribution for thermal exchange was very selective, favouring the o-and p-isomers. They have recently extended their studies to different mixtures of isomeric C 6 H 4 C1X (X = F, CI, CH 3 , CF 3 ) compounds to obtain more information on aspects such as relative rates and selectivity for exchange [8].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, httle is known about the reactions of recoil atoms, produced by radiative neutron capture, in such systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%